MENINGKATKAN KEMAMPUAN MENGAPRESIASI BACAAN CERITA SISWA KELAS IV SEKOLAH DASAR MELALUI PENDEKATAN AREA ISI - Alya Aulia Faiza; Urifatus Sa’diyah (Yayasan Citra Dharma Cindekia, 2025)
The general objective of this study was to improve the ability of fifth-grade elementary school students to appreciate narrative texts through a content-based approach. Specifically, the study aimed to assess students' ability to identify the elements constituting a story and the values ​​contained within it, as well as their ability to provide written responses regarding the story's content. Following the implementation of the content-based approach in literature appreciation lessons, the results were as follows: (1) 80% of the students correctly identified the elements constituting the story; (2) 75% of the students correctly identified the values ​​contained in the story; and (3) 80% of the students provided written responses regarding the story's content using clear, chronological language.